2015
DOI: 10.1039/c5sm01444a
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the free energy of adsorption of a polypeptide on amorphous SiO2from molecular dynamics simulations and force spectroscopy experiments

Abstract: Estimating the free energy of adsorption of materials-binding peptides is fundamental to quantify their interactions across bio/inorganic interfaces, but is difficult to achieve both experimentally and theoretically. We employ a combination of molecular dynamics (MD) simulations and dynamical force-spectroscopy experiments based on atomic force microscopy (AFM) to estimate the free energy of adsorption ΔGads of a (GCRL) tetrapeptide on amorphous SiO2 in pure water. The results of both equilibrium, advanced sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 77 publications
4
41
0
Order By: Relevance
“…The stretching of protein barnase by way of optical tweezers gives work values of over 1000 k B T 56 and the authors comment on different contributing factors. A study of short peptide's adsorption on amorphous SiO 2 shows that a friction emerging from pulling a peptide through water contributes to work in a linear way, quickly rising with dragging speed 57 , while maximum work of pulling 18 residue-long pVEC peptide variants through the POPE bilayer has been estimated to be between 797 and 919 kcal/mol 58 . As it is, work values, we have arrived at, are within expectations for this type of simulation.…”
Section: Resultsmentioning
confidence: 99%
“…The stretching of protein barnase by way of optical tweezers gives work values of over 1000 k B T 56 and the authors comment on different contributing factors. A study of short peptide's adsorption on amorphous SiO 2 shows that a friction emerging from pulling a peptide through water contributes to work in a linear way, quickly rising with dragging speed 57 , while maximum work of pulling 18 residue-long pVEC peptide variants through the POPE bilayer has been estimated to be between 797 and 919 kcal/mol 58 . As it is, work values, we have arrived at, are within expectations for this type of simulation.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Wei et al demonstrated the surface functionalization of AFM Si 3 N 4 tips with a facile method for binding DNA, peptide and proteins for the SMFS determination of the interactions between biomolecules and various materials [22,23,32]. As shown in Figure 1a, the Si 3 N 4 tip was first modified with 3-aminopropyl triethoxysilane (APTES) and thiethoxychorosilane (TTCS) through the silanization to form -NH 2 group on the surface of the tip, which could further react with the bifunctional N-hydroxysuccimidyl (NHS)-PEG-NHS ester disulfide to provide the -NH 2 -binding groups on the tip.…”
Section: Tip Functionalizationmentioning
confidence: 99%
“…Previously, various famous nanomaterials including metallic nanoparticles [15], carbon nanotubes [16], graphene [17], and other two-dimensional nanomaterials [18], have been conjugated with proteins, peptides, DNA/ RNA, enzymes and others for realizing the bio-applications in bionanotechnology, biomedicine and tissue engineering. It is well known that the formation of stable bio-hybrids is based on the interaction forces between biomolecules and the materials interfaces, which could be measured experimentally and theoretically by using some techniques such as optical tweezers and fluorescent spectroscopy [19], calorimetry titration [20], polymerase chain reaction [21], force spectroscopy (FD) [22], and molecular dynamic simulations [23].…”
Section: Introductionmentioning
confidence: 99%
“…Single-molecule force spectroscopy (SMFS), using an AFM, can directly measure the interactions between an amino acid or a peptide with a substrate. 19,20,21,22,23,24,25,26 Other methods such as phage display, 27,28 quartz crystal microbalance (QCM) 29 or surface plasmon resonance (SPR) 29,30,31,32,33 measure the interactions of peptides and proteins to inorganic surfaces in bulk. 34,35,36 This means that the results obtained by these methods relate to ensembles of molecules or aggregates.…”
Section: 161718mentioning
confidence: 99%